Hubungan Pengetahuan Keluarga tentang Kesehatan Jiwa dengan Penerimaan Terhadap Anggota Keluarga ODGJ di Wilayah Kerja Puskesmas Ciherang - Gina Sukriyah Amala; Sifa Fauziah; Shinta Arini Ayu (Malahayati Nursing Journal, 2026)
ABSTRACT Mental health is a state of well-being that enables individuals to develop optimally. In the work area of Ciherang Community Health Center, there was a decrease in visits by patients with mental disorders (ODGJ), which is suspected to be related to the family's understanding and acceptance. This study aims to determine the relationship between family knowledge about mental health and acceptance of family members with ODGJ in the work area of Ciherang Community Health Center. This quantitative research used a correlational design with a cross-sectional approach. The sample consisted of 94 respondents selected through purposive sampling. Data were collected using the Mental Health Knowledge Schedule (MAKS) and the Family Attitude Scale (FAS) questionnaires. Data analysis was performed using the Spearman Rank correlation test. Most respondents had a sufficient level of knowledge (63.8%) and a high level of acceptance (86.2%). The bivariate analysis showed a significance value of 0.555 (p 0.05) with a correlation coefficient (R) of -0.062. There is no significant relationship between family knowledge about mental health and acceptance of family members with ODGJ. Acceptance is more likely influenced by affective factors such as affection and moral responsibility rather than clinical knowledge alone. Keywords: Family Knowledge, Acceptance, ODGJ, Mental Health. ABSTRAK Kesehatan jiwa merupakan kondisi kesejahteraan yang memungkinkan individu berkembang optimal. Di wilayah kerja Puskesmas Ciherang, ditemukan adanya penurunan kunjungan pasien ODGJ yang diduga berkaitan dengan faktor pemahaman dan penerimaan keluarga. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan keluarga tentang kesehatan jiwa dengan penerimaan terhadap anggota keluarga ODGJ di wilayah kerja Puskesmas Ciherang. Penelitian kuantitatif ini menggunakan desain korelasional dengan pendekatan cross-sectional. Sampel berjumlah 94 responden yang dipilih melalui teknik purposive sampling. Pengumpulan data menggunakan kuesioner Mental Health Knowledge Schedule (MAKS) dan Family Attitude Scale (FAS). Analisis data dilakukan dengan uji korelasi Spearman Rank. Mayoritas responden memiliki tingkat pengetahuan dalam kategori cukup (63,8%) dan tingkat penerimaan dalam kategori tinggi (86,2%). Hasil analisis bivariat menunjukkan nilai signifikansi sebesar 0,555 (p 0,05) dengan nilai koefisien korelasi (R) sebesar -0,062. Tidak terdapat hubungan yang signifikan antara pengetahuan keluarga tentang kesehatan jiwa dengan penerimaan terhadap anggota keluarga ODGJ. Penerimaan keluarga lebih banyak dipengaruhi oleh faktor afektif seperti kasih sayang dan tanggung jawab moral dibandingkan hanya sekadar pengetahuan klinis. Kata Kunci: Pengetahuan Keluarga, Penerimaan, ODGJ, Kesehatan Jiwa.